Revisiting Arabic Grammar Instruction: An Experimental Study on the Pedagogical Application of Antoun Dahdah’s Linguistic Framework - Gilang Mahirul Mursyid (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
Arabic grammar instruction is often perceived as complex and cognitively demanding due to its abstract and rule-based nature. This study revisits Arabic grammar instruction by examining the pedagogical application of Antoun Dahdahâ€™s linguistic framework, which emphasizes the visual and systematic organization of grammatical rules. Using a quasi-experimental design, the study was conducted at a public Islamic senior high school (MAN 1 Lamongan, Indonesia) and involved two intact eleventh-grade classes: an experimental group taught using Dahdahâ€™s framework and a control group taught through conventional instruction. The instructional focus was on fiÊ¿l muá¸ÄriÊ¿ mansÅ«b and majzÅ«m. Data were collected through pre-tests and post-tests to measure grammar achievement and a questionnaire to examine studentsâ€™ perceptions. The results showed a significant difference in post-test scores in favor of the experimental group. Normalized gain analysis indicated that the Dahdah-based instruction was moderately effective in improving studentsâ€™ grammatical competence. In addition, students reported highly positive perceptions toward the clarity and organization of the instructional framework. These findings suggest that Antoun Dahdahâ€™s linguistic framework offers a pedagogically valuable approach to reorganizing Arabic grammar instruction in secondary education.